ANALISIS PENERAPAN SISTEM PENGENDALIAN INTERN PEMERINTAH (SPIP) - Achmad Nasution (JI@P, 2016)
This research aimed the application of government internal control system inInspectorate Office of Boyolali Regency. Five elements that were studied are: (1)Environment of control; (2) Evaluation of risk; (3) Activity of control; Informationand communication; and (5) internal control monitoring. Case study method wasused in this study. Interview, document study, and observation data gatheringtechniques were used for colleting the needed data. Validity of the finding wassupported by the data or resource triangulation method. Interactive analysismodel consisting of three elements i.e. data reduction, data display, andverification and conclusion drawing was used to analyse the data. Researchresult indicated that the application of government internal control system inInspectorate Office in Boyolali Regency had already implemented properly. Thedata showed, however, that there were some weaknesses especially related toinfornation and communication aspect. It was found that there were no directaccessable media such as box office, box for community suggestion,whistleblower system, inspectorate website, and others. The success of theapplication of the system depends on the ordinates commitment in particularlyand community participation in general. By doing so, good governance that isfree from collusion, corruptin, and nepotism can be realized.Key words: Good Governance, government internal control system.